Oxidative Coupling of N-Methoxyamides and Related Compounds toward Aromatic Hydrocarbons by Designer μ-Oxo Hypervalent Iodine Catalyst - Dohi, Toshifumi; Sasa, Hirotaka; Dochi, Mio; Yasui, Chihiro; Kita, Yasuyuki (Synthesis, 2019)
Oxidative coupling strategies that can directly convert the C–H group for chemical transformations are, in theory, ideal synthetic methods to reduce the number of synthetic steps and byproduct generation. Hypervalent iodine reagents have now become one of the most promising tools in developing oxidative couplings due to their unique reactivities that are replacing metal oxidants. As part of our continuous development of oxidative coupling reactions, we describe in this report highly efficient μ-oxo hypervalent iodine catalysts for the direct oxidative coupling of N-methoxyamides and related compounds with aromatic hydrocarbons. The excellent TONs, up to over 100 times, with a best catalyst loading of 0.5 mol% were determined for the oxidative C–H/N–H coupling method, which can provide the most straightforward route to obtaining these unique arylamide compounds.
Keywords: hypervalent compound; iodine; oxidative coupling; amidation; electrophilic substitution